2007
DOI: 10.1902/jop.2007.070135
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Fluid Levels of Leukotriene B4 in Periodontal Health and Disease

Abstract: The substantial increase in GCF LTB(4) concentrations with the severity of periodontal disease and a concomitant decrease in its level following SRP in subjects with periodontitis suggest a possible role for LTB(4) in the progression of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
22
0
4
Order By: Relevance
“…During the 3 years of function, we found that the amounts of histamine, PGE 2 , LTB4, and 12‐HETE were significantly higher, whereas the levels of 15‐HETE, a well‐known anti‐inflammatory agent, were markedly lower in the SI group compared to the NSI group ( P <0.05 at 12 months; P <0.01 at 24 and 36 months). Based on data in the literature, 14–28 the levels of histamine and arachidonic acid metabolites in the SI group may be associated with tissue inflammation, as confirmed by the strong correlation observed at 24 and 36 months with all clinical indices evaluated ( P <0.001). Of particular value are the data we obtained about the behavior of LTB4 and PGE 2 , arachidonic acid–derived products that have potent proinflammatory and immunomodulatory effects 37 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…During the 3 years of function, we found that the amounts of histamine, PGE 2 , LTB4, and 12‐HETE were significantly higher, whereas the levels of 15‐HETE, a well‐known anti‐inflammatory agent, were markedly lower in the SI group compared to the NSI group ( P <0.05 at 12 months; P <0.01 at 24 and 36 months). Based on data in the literature, 14–28 the levels of histamine and arachidonic acid metabolites in the SI group may be associated with tissue inflammation, as confirmed by the strong correlation observed at 24 and 36 months with all clinical indices evaluated ( P <0.001). Of particular value are the data we obtained about the behavior of LTB4 and PGE 2 , arachidonic acid–derived products that have potent proinflammatory and immunomodulatory effects 37 .…”
Section: Discussionmentioning
confidence: 69%
“…Recently, a study 16 by the authors showed that histamine may serve as a predictive or prognostic index of periodontal disease because its increase precedes the onset of clinical signs of periodontal disease and is correlated with the severity of inflammation. Gingival crevicular fluid in chronic periodontitis contains high levels of leukotriene B4 (LTB4), 17 a potent chemoattractant mediator 18,19 . Several studies indicated that prostaglandin E 2 (PGE 2 ) is involved in the pathogenesis of periodontal disease 20–22 and destruction 23 .…”
mentioning
confidence: 99%
“…For example, leukotriene B 4 (LTB 4 ) is a lipid mediator formed from arachidonic acid and is one of the most potent stimulants of macrophages. LTB 4 levels in gingival crevicular fluid correlate with periodontitis severity [36]. LTB 4 enhances the generation of miR-155 to promote MyD88-dependent macrophage activation [37].…”
Section: Osteoclasts and Mirnasmentioning
confidence: 99%
“…, Moura et al., ), but the exact mechanism is still unclear. Moreover, increased concentration of LTB4 in gingival crevicular fluid (GCF) has been associated with the severity of PD (Pradeep et al., ). Another bioactive mediator derived from membrane‐bound phospholipids, platelet‐activating factor (PAF), is known to control osteoclast activity and to play a role in periodontal infection (Madeira, Queiroz‐Junior, Costa et al.…”
Section: Introductionmentioning
confidence: 99%